The Coupling Coordination Degree between Tourism and Urbanization in Rural Revitalization: A Case Study of the Wuling Mountain Area - Xiang, Shilei; Li, Yangkuo; Tian, Robert Guang (Advances in Social Sciences Research Journal, 2023)
Regional coordinated development should be promoted for high-quality economic development. An effective way for regional economic development is to enhance the coupling coordination degree development of tourism and urbanization. This paper reviews the literature on the coupling coordination degree between tourism and urbanization. Moreover, it collates and analyzes the literature on tourism development and urbanization in the Wuling Mountain Area. It explores the evaluation index system and development mechanism of the coupling coordination degree of tourism and urbanization in the area. It proposes countermeasures for improving the coupling coordination degree of tourism and urbanization. Thus, China's regional economy and society can develop faster and more harmoniously.